THE METHODOLOGY OF DATA BACKUP AND RECOVERY FOR COMPUTERS RUNNING ON WINDOWS (Modern information system and technologies, 2018)
The article discusses the need for using backup and recovery systems that are an effective means of protecting corporate resources. Backup and recovery technologies allow you to protect data and help you save time and financial costs significantly in restoring the health of your information infrastructure in case of unforeseen circumstances.